1980
DOI: 10.2134/jeq1980.00472425000900030038x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Loss and Microbiological Quality of Runoff from Land Treated with Poultry Litter

Abstract: Because large amounts of poultry wastes are often applied to hilly land in the southeastern United States, information is needed on the environmental hazards of this practice. A rainfall simulator was used to study the effect of application of poultry litter (manure plus wood residues) on runoff water quality and soil loss, on moderately sloping (7%) land. Increasing rates of litter were surface-applied on fallow soil and grassland and also incorporated in the fallow soil. Runoff and soil loss were drastically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…Scrutinizing results (Table 2) showed that the manure treatment essentially reduced sediment concentration and soil loss (Mitchell and Gunther, 1976;Giddens and Barnett, 1980;Gilley and Eghball, 1998;Gilley and Risse, 2000;MartinezCasanovas, 2006 andRees et al, 2011). The manure could also reduce soil loss because runoff amount and rainfall detachment were diminished and soil infiltration rates increased.…”
Section: Manure Mulchmentioning
confidence: 96%
See 1 more Smart Citation
“…Scrutinizing results (Table 2) showed that the manure treatment essentially reduced sediment concentration and soil loss (Mitchell and Gunther, 1976;Giddens and Barnett, 1980;Gilley and Eghball, 1998;Gilley and Risse, 2000;MartinezCasanovas, 2006 andRees et al, 2011). The manure could also reduce soil loss because runoff amount and rainfall detachment were diminished and soil infiltration rates increased.…”
Section: Manure Mulchmentioning
confidence: 96%
“…Mitchell and Gunther (1976) verified that the liquid manure provided a stabilizing effect on the soil surface, resulting in reduced rates of runoff and erosion. Giddens and Barnett (1980) revealed that the poultry litter could substantially reduce soil loss. Gilley and Eghball (1998) used beef cattle manure to control sediment transport and found that the manure could significantly reduce solids transport.…”
Section: Introductionmentioning
confidence: 99%
“…The most common use for this waste litter is direct application to agricultural land. Poor management of land application has long been recognized as detrimental to the environment and fish, animal, and human health (8,12,20,22). A report by the U.S. Senate Committee on Agriculture, Nutrition and Forestry in 1997 (23) identified nutrient runoff from livestock and poultry as the greatest pollutant in 60% of rivers and streams identified by the U.S. Environmental Protection Agency as having impaired water quality.…”
mentioning
confidence: 99%
“…A rainfall simulator was used by Giddens and Barnett (1980) to investigate runoff and soil loss as affected by the application of poultry litter. Litter application on fallow soil substantially reduced runoff and soil loss.…”
mentioning
confidence: 99%